2023
DOI: 10.3390/ijms24086959
|View full text |Cite
|
Sign up to set email alerts
|

The “Asthma-Polycystic Ovary Overlap Syndrome” and the Therapeutic Role of Myo-Inositol

Abstract: Asthma is a heterogeneous inflammatory disease characterized by abnormalities in immune response. Due to the inherent complexity of the disease and the presence of comorbidities, asthma control is often difficult to obtain. In asthmatic patients, an increased prevalence of irregular menstrual cycles, infertility, obesity, and insulin resistance has been reported. Given that these conditions are also common in patients with polycystic ovary syndrome (PCOS), we propose the definition of “asthma-PCOS overlap synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 125 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…An increased prevalence of menstrual dysfunction, infertility, obesity, and insulin resistance has been reported in women with asthma. 119 , 120 , 121 The link between asthma and PCOS is proposed to occur via inflammatory pathways that are shared in obesity and insulin resistance. 119 , 120 , 121 Those with PCOS appear to have a higher risk of developing asthma, and the level of use of asthma medication prescriptions is reported to be higher in those with PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased prevalence of menstrual dysfunction, infertility, obesity, and insulin resistance has been reported in women with asthma. 119 , 120 , 121 The link between asthma and PCOS is proposed to occur via inflammatory pathways that are shared in obesity and insulin resistance. 119 , 120 , 121 Those with PCOS appear to have a higher risk of developing asthma, and the level of use of asthma medication prescriptions is reported to be higher in those with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“… 119 , 120 , 121 The link between asthma and PCOS is proposed to occur via inflammatory pathways that are shared in obesity and insulin resistance. 119 , 120 , 121 Those with PCOS appear to have a higher risk of developing asthma, and the level of use of asthma medication prescriptions is reported to be higher in those with PCOS. 32 , 122 In a Danish cohort, asthma had a prevalence of 25% in those with PCOS who were aged 12-60 years.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established the association between PCOS and subsequent asthma among reproductive-aged females ( 12 14 ). There is clinical overlap between asthma and PCOS ( 15 ), including alterations in gut microbiota ( 16 18 ), menstrual cycle abnormalities ( 19 21 ), infertility ( 22 , 23 ), obesity ( 24 – 26 ), and insulin resistance that was found in asthmatics as well as females with PCOS ( 27 , 28 ). Previous epidemiological studies have also found an association between PCOS and subsequent asthma ( 13 , 29 ).…”
Section: Introductionmentioning
confidence: 99%